Laparoscopic Distal Pancreatectomy - Sherwinter, Danny A (Society of Laparoendoscopic Surgeons, 2012)
BACKGROUND: Laparoscopic management of distal pancreatic malignancies has been slow to gain a foothold in all but high-volume tertiary referral centers. The aim of this study was to assess the safety and outcomes of laparoscopic distal pancreatectomy (LDP) performed in a low-volume community hospital by a diverse group of surgeons, none of whom have a specialized laparoscopic background. METHODS: We conducted a retrospective review of all patients who underwent open distal pancreatectomies (ODPs) and LDPs between August 2001 and June 2008. Data included type of surgery, open versus laparoscopy, demographics, operative time, blood loss, length of hospital stay, histopathologic diagnosis, postoperative complications, American Society of Anesthesiologists score, and mortality. RESULTS: Twenty-seven patients with pancreatic masses underwent distal pancreatic resection during the study period. Fifty-nine percent (n = 16) underwent LDP, and 41% (n = 11) underwent ODP. Mean patient age was 66 y (range, 40 to 86) for the LDP group and 62 (range, 40 to 84) for the ODP group. Mean operative time was 231 min (range, 195 to 305) for LDP and 240 (range, 150 to 210) for the ODP technique. Mean length of stay for LDP and ODP was 8 (range, 3 to 22) and 12 d (range, 5 to 2), respectively. Morbidity was 25% (n = 4) in the LDP group and 36% (n = 4) in the ODP group. None of the differences between the LDP and ODP groups were statistically significant. No mortalities occurred in either group. CONCLUSION: This study supports the idea that LDP can be safely and effectively performed by any surgeon comfortable with basic laparoscopy and may not require specialized training or a specialized center. Further data are required to make more definitive conclusions.